Herbage accumulation dynamics in mixed pastures composed of kikuyugrass and tall fescue as affected by grazing management - Bernardon A.* (2021)
© 2021 John Wiley & Sons Ltd.A less-explored alternative to animal production in the subtropics is a mixture of perennial cool- and warm-season forage grasses. This study aimed to determine a grazing management strategy to enhance forage production and attenuate the seasonality of a mixed pasture composed of kikuyugrass (Pennisetum clandestinum) and tall fescue (Festuca arundinacea). Four treatments were implemented in a completely randomized block design using a factorial scheme (2 × 2) with three replicates. The factorial arrangement consisted of two canopy heights (12 and 17 cm) associated with or without a single autumn grazing of 7 cm. Evaluations were conducted over 2 years. Nitrogen fertilization was performed only during the winter and spring seasons. Regardless of grazing height targets (12 or 17 cm), severe defoliation in autumn increased forage accumulation by 10% in mixed pastures composed of kikuyugrass and tall fescue; however, such management strategy should not be recommended because it delayed canopy recovery by 90–120 days, restrained winter grazing, and, paradoxically, increased forage production seasonality. Tall fescue was the dominant species in all treatments in the second year of evaluation, and we hypothesized that the lack of N fertilization during the summer impaired the persistence of kikuyugrass and was the main reason for this dominance effect. Therefore, we suggest evaluating summer N fertilization strategies, which could benefit both species and ensure the persistence of kikuyugrass in the mixture.